Non-coding RNA Contribution to Thoracic and Abdominal Aortic Aneurysm Disease Development and Progression - Li, Yuhuang; Maegdefessel, Lars (Frontiers in Physiology, 2017)
Multiple research groups have started to uncover the complex genetic and epigenetic machinery necessary to maintain cardiovascular homeostasis. In particular, the key contribution of non-coding RNAs (ncRNAs) in regulating gene expression has recently received great attention. Aneurysms in varying locations of the aorta are defined as permanent dilations, predisposing to the fatal consequence of rupture. The diagnosis of an aneurysm is commonly an accidental finding, although there is an increasing number of screening programs targeting high-risk populations. The most feared clinical consequence of aneurysm progression is acute rupture, which carries the burden of a huge mortality. Interestingly, sixty percent of patients with aneurysms die of other cardiovascular causes, such as stroke or myocardial infarction, suggesting a relationship between AAAs and atherosclerosis. The characteristic pathology of an aneurysm is characterized by progressive vessel wall dilation, promoted by dying vascular smooth muscle cells and limited proliferation, as well as impaired synthesis and degradation of extracellular matrix components, which at least partially is the result of transmural inflammation and its disruptive effect on vessel wall homeostasis. In the recent past, several non-coding RNAs (mainly microRNAs) have been discovered as being involved in aneurysm progression throughout varying locations of the aorta. Purpose of this current review is to summarize these current findings, and to put them into perspective of potential therapeutic and biomarker applications in the future.